PROBLEMATIKA PEREMPUAN: PRESENTASI KEKERASAN GENDER PADA CERPEN “LINTAH” DAN “MENYUSU AYAH” KARYA DJENAR MAESA AYU - Rizki Amalia Sholihah (Sirok Bastra, 2013)
Instance of this use of gender violence found in “Lintah” and “Menyusu Ayah” short stories is caused existenceassumption that women are the objects of the society from the violence. Female considered as being number twocan only serve as a means of satisfying men and can not issue an opinion. Besides women's capacity to survive indeterioration and not fighting is the most powerful weapon to make the men feel to win without having to give ameaningful match. Presentation of sexual violence found in short stories "Lintah" and “Menyusu ayah" occurs intwo forms. Namely sexual and non sexual. In non-sexual forms are also divided further in terms of physical andspiritual. Sexual violence as a form of sexual harassment and rape experienced by Maha and Nayla, whereasnonsexual violence in terms of physical form of beatings received by the two leaders. As for the inner side, theinner repression of the characters that makes them depressed.